PENGARU EDUKASI DIET DIABETESMELITUS MENGGUNAKAN VIDEO TERHADAP KONTROL GLUKOSA DARAH PADA PASIEN DIABETES MELITUS - Dwi Retno Sulistyaningsih; Retno Setyawati; Ikoh Ropikoh (Universitas Muhammadiyah Klaten, 2025)
Background: Diabetes mellitus is a non-communicable disease whose prevalence is increasing worldwide. Diabetes can affect various organ systems of the human body, causing macrovascular and microvascular complications. There are several methods that can be used in providing information, one of which is education in the form of videos. Methods: This study used a quasi-experimental design with a control group design pre- posttest data taken from these two groups using purvosive sampling techniques. Results: based on the results of the analysis, most of the respondents were between the ages of 56-65 in the intervention group (44.4%), and the control group (50.0%). with the majority gender of women in the intervention group 72.2%, and in the control group 66.7%. the education level category is elementary school intervention group 50.0%, and control group of 11 people 61.1%. The work was mostly IRT of the intervention group and the control group of 55.6%. Patients suffering from DM most often suffered from DM in the range of 1-5 years, the intervention group was 94.4%, and the control group was 83.3%. Conclusion: There is a significant influence on diabetes mellitus diet education using video on blood glucose control in patients with diabetes mellitus with a p value of 0.0001 at RSI Sultan Agung Semarang.